Relative Efficiency Of Sterilization Methods For The Treatment Of Glassware Part Of Artificial Vagina To Be Used For Bovine Semen Collection (Applied Biological Research, 2014)
Present investigation was conducted on Sahiwal, HF crosses and  Murrah bulls maintained at A.B. Complex, NDRI, Karnal (India) to  identify the relative efficiency of various sterilization methods for the  treatment of artificial vagina (AV) to be used for bovine semen  processing. The glassware part of AV was sterilized by hot air oven at  1600C for 60 min. and microwave oven for 3 min. A total of 72 ejaculates  were taken from 3 collections each from 4 bulls of each breed/species  subjected to 2 types of treatments, then total plate count (TPC) of all  these combinations was carried out using plate count agar media.  Standardization of the best sterilizing method was done by selecting the  method whose total bacterial count on the media was the least and the  best semen quality (mass activity, initial motility, non-eosinophilic  percent and abnormalities) was obtained. The microwave oven method of sterilization of glassware part of artificial vagina was found superior  over hot air oven method.
Keywords: Artificial vagina; bovine semen; sterilization methods